A Comparative Analysis of the US vs EU Private Equity Markets - Wallace, Colton (My University, 2025)
This project offers a comparative analysis of the private equity markets in the United States and the European Union, concentrating on the environments for fundraising, investing, and divesting, as well as broader economic factors. Notably, the EU private equity market experienced a 15% increase in capital raised during the first half of 2024, fueled by decreasing interest rates and a stabilizing macroeconomic landscape (Invest Europe, 2024). In contrast, the US market contends with higher tariff regulations and slower divestment activity, though it maintains resilience in sectors such as healthcare and consumer goods (PitchBook, 2024). Investment activity in Europe is gaining momentum, especially within the AI and defense sectors, with a favorable outlook for mergers and acquisitions anticipated in 2025 (PitchBook, 2024). While the US market remains strong, it is marked by conservative leverage ratios and a trend toward growth equity deals instead of leveraged buyouts (PitchBook, 2024). European divestment activity, although initially sluggish, is beginning to accelerate, potentially unlocking further fundraising and investment opportunities (Invest Europe, 2024). The US market is still recovering from the prolonged effects of inflation and unfavorable valuation trends, with exit activity falling below pre-COVID levels in 2023 (PitchBook, 2024). The quantitative analysis reveals differences in performance metrics such as IRR, TVPI, and DPI, with the EU market demonstrating a more stable recovery (Burgess, 2024). Strategic recommendations highlight the importance of targeting high-growth sectors, leveraging regional strengths, and diversifying investment strategies. This project emphasizes the dynamic nature of private equity markets and provides valuable insights for investors navigating the complexities of the investment landscapes in the US and EU.